ESTIMATING THE CONCENTRATION OF NO2 WITH THE COKRIGING METHOD IN THE CAPITAL CITY OF JAKARTA - Saifudin, Toha; Faiza, Atikah; Puspasari, Laili; Nurrohmah, Zidni 'Ilmatun (PATTIMURA UNIVERSITY, 2023)
The increase in transportation activities is the leading cause of the emergence of the air pollution risk, which harms public health. especially in big cities. Nitrogen Dioxide (NO2) gas is one of the critical factors explaining air pollution. NO2 contributes to particle pollution and acid deposits and is a precursor of ozone, the leading cause of photochemical smog. Meanwhile, Sulfur Dioxide (SO2) is another substance that is a source of pollutants and can cause acid rain and aerosolized sulfate particle pollution. Therefore, it is necessary to estimate the concentration of pollutants, especially NO2. One method that can be used in this estimation is Cokriging, which considers secondary variables to record primary variables. Based on the results obtained, the Cokriging analysis shows that the estimation of NO2 content in the five predicted areas, namely Tanjung Priok, Johar Baru, Gelora Bung Karno, Pancoran, Halim Perdanakusuma, has a quality standard value below 80 µppm (quality standard value set by the BMKG). In summary, the research unveils variations in SO2 and NO2 levels across distinct regions in Jakarta, with Monas recording the highest SO2 levels (10 μppm), while Grogol exhibits the lowest NO2 levels (16 μppm). The average SO2 level among all surveyed areas is 5.875 μppm, while NO2 averages 17.375 μppm. These findings emphasize the pressing need to implement measures aimed at preserving air quality within the limits established by government standards. Additionally, Cokriging estimates reveal that the content of NO2 in Tanjung Priok, a coastal area, significantly deviates from estimations in other Jakarta areas and ranks as the highest among the locations studied, with GBK displaying the lowest content.